PENGALIHAN EKSPOR MINYAK SAWIT DARI PASAR INTERNASIONAL KE PASAR DOMESTIK - Fakhrurrazi Fakhrurrazi; Cut Zakia Rizki (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
Abstract This study aims to determine the projection of biodiesel consumption in Indonesia. The data in this study uses secondary data in the form of monthly data from 2014-2020 obtained from the ministry of energy and mineral resources. The method used in this study is the ARIMA method, which is an autoregressive (AR), moving average (MA) model and a mixed model of ARIMA (autoregressive moving average), the model used to project is the MA model. The forecasting results show that the policy of diverting the palm oil market to domestic markets will have a positive and effective impact on the government in producing large quantities of biodiesel. Therefore, it is suggested that the government should encourage the public to increase biodiesel consumption along with the increase in per capita income, one of which is by promoting biodiesel as an environmentally friendly product.Keywords: Consumption, Biodiesel, Arima